A prospective evaluation of urinary tract infection among children: An institutional-based study - Agarwal, Monica (Indian Journal of Child Health, 2019)
Background: One of the common health problems affecting significant pediatric population is urinary tract infection (UTI). Due to the presence of non-specific signs and symptoms, it is very difficult to diagnose UTI in children. Objective: The objective of this study was to assess the clinical profile and risk factors of UTI among pediatric patients. Materials and Methods: It was a prospective study where a total of 50 children with UTI were included in the study. A self-framed questionnaire was given to all the pediatric subjects and their parents/guardians for recording the clinical profile and medical history. Various risk factors for the occurrence of UTIs were recorded and assessed. All the results were analyzed by SPSS software. Results: A total of 52% of the subjects were having rural residence. Hospitalization in the past 2 months was present in 10% of the patients. Constipation was a risk factor in 16% of patients. Reduced water and neglected cleaning habit were found to be a risk factor in 24% and 40% of patients. Common toilet was a risk factor in 18% of the patients. Conclusion: UTI represents a significant health problem among pediatric population. The use of common toilet, improper cleaning, and prolonged hospitalization is among the prominent risk factors associated with it.